Product and Process Innovations in the Life Cycle of an Industry - Darren Filson (Claremont McKenna College, Department of Economics, 2000)
Filson (2001) uses industry-level data on firm numbers, price, quantity, and quality along with an equilibrium model of industry evolution to estimate the nature and effects of quality and cost improvement in the personal computer industry and four other new industries. This paper studies the person computer industry in more detail and shows that the model explains some peculiar patterns that cannot be explained by previous life-cycle models. The model's estimates are evaluated using historical studies on the evolution of the personal computer industry, and patterns that require further model development are described.
Keywords: L10; L63; O31; 330; technology; technological change; industry dynamics; personal computer market; microelectronics